(untitled) (Eurasian Journal of Learning and Academic Teaching, 2023)
In this article, based on the analyzes available in modern psychological-pedagogical literature and scientific publications, recommendations were developed for the development of technology for organizing independent work of students in the subjects of teaching foreign languages. Since two subjects are involved in this process: the teacher and the student, we consider it appropriate to develop an algorithm for each activity. For teachers, we identified the following main stages: informational, operational, feedback, and control stage. Algorithm of student activity: understanding and understanding of the task, work planning, direct activity, self-control, self-esteem, self-awareness. The article presents examples of the use of different forms of organizing students’ independent work: individual, group as an example of the subject "Integrated course of teaching foreign languages"